Socially Optimal Mistakes? Debiasing COVID-19 Mortality Risk Perceptions and Prosocial Behavior - Martin Abel; Tanya Byker; Jeffrey P. Carpenter (Institute of Labor Economics (IZA), 2020)
The perception of risk affects how people behave during crises. We conduct a series of experiments to explore how people form COVID-19 mortality risk beliefs and the implications for prosocial behavior. We first document that people overestimate their own risk and that of young people, while underestimating the risk old people face. We show that the availability heuristic contributes to these biased beliefs. Using information about the actual risk to debias people's own risk perception does not affect donations to the Centers for Disease Control but does decrease the amount of time invested in learning how to protect older people. This constitutes a debiasing social dilemma. Additionally providing information on the risk for the elderly, however, counteracts these negative effects. Importantly, debiasing seems to operate through the subjective categorization of and emotional response to new information.
Keywords: C91; D91; H41; 330; risk perception; prosocial behavior; debiasing; experiment